WUJUD KEPEDULIAN KKN-DR KELOMPOK 7 UIN SU TERHADAP WABAH COVID-19 DI DESA SEI MENCIRIM KUTALIMBU - yayang safitri; Naryama Harahap; Khairul Purqon; Winda Kustiawan (Aptekmas Jurnal Pengabdian pada Masyarakat, 2021)
Prevention of the spread and increase of Covid 19 in Indonesia requires support from various parties, one of which is from students through the Real Work Lecture (KKN) program. Group 7 KKN DR UINSU distributed masks and free hand soap to residents of Sei Mencharim Village, Kutalimbaru. The distribution of masks and hand soap is based on the lack of awareness of the community in the village in carrying out health protocols when they do activities outside the home. The distribution of masks and hand washing soap will be carried out on August 1, 2021 and August 09, 2021 on village streets, where villagers pass by to travel and to people's homes. The target of this activity is all people who live in Sei Mencharim Village. The method used is the distribution of masks and hand washing soap to all people on the highway and to residents' homes. In addition, socialization was also carried out when masks and hand washing soap were given to residents. The socialization consisted of an explanation on how to wash hands using the correct soap and the time limit for using masks. As a result, this activity was able to provide awareness to the public about the importance of following the existing Covid 19 health protocols and controlling the spread of Covid-19 in Sei Mencharim village in general.